2002
DOI: 10.1095/biolreprod67.1.154
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor Enhances Expression of Connexin 43 Protein in Cultured Porcine Preantral Follicles1

Abstract: Connexin 43 (Cx43) and gap junctional coupling appear to play a critical role in early follicular development because absence of Cx43 disrupts progression of follicles beyond primary stages in transgenic mouse ovaries. Two experimental culture systems were used to determine whether epidermal growth factor (EGF) stimulates expression of Cx43 in early porcine follicular development. Ovarian explants were collected from 32- to 40-day-old gilts and cultured for 6 days on membrane inserts in Waymouth MB 752/1 mediu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 59 publications
0
19
1
Order By: Relevance
“…EGF has been shown to positively or negatively regulate Cx43 expression depending on the cell type in question. Stimulatory effects of EGF on Cx43 have been described in porcine preantral follicles, rat granulosa cells, human kidney epithelial cells, human neural progenitor cells, and glioblastoma cells (Rivedal et al, ; Bolamba et al, ; Kennedy et al, ; Lemcke and Kuznetsov, ; Munoz et al, ); whereas suppressive effects have been observed in rat astrocytes and liver epithelial cells (Ueki et al, ; Leithe and Rivedal, ). In keeping with the cell context‐dependent regulation of Cx43 by EGF, multiple signaling pathways have been variably described to mediate both positive and negative effects.…”
Section: Discussionmentioning
confidence: 99%
“…EGF has been shown to positively or negatively regulate Cx43 expression depending on the cell type in question. Stimulatory effects of EGF on Cx43 have been described in porcine preantral follicles, rat granulosa cells, human kidney epithelial cells, human neural progenitor cells, and glioblastoma cells (Rivedal et al, ; Bolamba et al, ; Kennedy et al, ; Lemcke and Kuznetsov, ; Munoz et al, ); whereas suppressive effects have been observed in rat astrocytes and liver epithelial cells (Ueki et al, ; Leithe and Rivedal, ). In keeping with the cell context‐dependent regulation of Cx43 by EGF, multiple signaling pathways have been variably described to mediate both positive and negative effects.…”
Section: Discussionmentioning
confidence: 99%
“…In the rat, several studies demonstrate that the connexin 43 gap junction protein is present in multiphosphorylated forms: the 43-kDa band represents the nonphosphorylated form, while the bands with the slightly retarded electrophoretic mobility represent the phosphorylated forms [57][58][59]. In porcine, immunoblot analysis revealed the presence of two immunoreactive bands of 43 and 45 kDa [60,61] or three bands of 43, 45, and 47 kDa [42]. The 43-kDa band is a nonphosphorylated band, whereas the 45-and 47-kDa bands are phosphorylated forms of this protein.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of a kidney epithelial cell line with EGF for 2-3 h was reported to stimulate the upregulation of gap junctional communication, which may be related to the synthesis or transport of Cx43 (Vikhamar, Rivedal, Mollerup, & Sanner, 1998). EGF was also found recently to increase the expression of Cx43 protein in porcine granulosa cells by two to five-fold (Bolamba, Floyd, McGlone, & Lee, 2002). This change occurred in the absence of changes in Cx43 phosphorylation and may be involved in the regulation of early folliculogenesis.…”
Section: Receptor Protein Tyrosine Kinases-in Many Cases Activation mentioning
confidence: 94%